The project management tool kit : 100 tips and techniques for getting the job done right - Kendrick, Tom (American Management Association, 2014)
Today's projects are more challenging than ever--and project managers need all the help they can get to succeed amid shifting priorities, budget cuts, interruptions, and other obstacles. Now in its third edition, The Project Management Tool Kit is a must-have strategic partner, filled with step-by-step guidance that will enable managers to get complex projects completed on time and on budget. Extensively updated and revised to reflect the latest changes to A Guide to the Project Management Body of Knowledge (PMBOK Guide), this results-oriented resource offers 100 powerful, practical tips and techniques.
Revised edition of: The project management tool kit : 100 tips and techniques for getting the job done right, 2nd ed.
Includes free sample chapter from Emotional Intelligence for Project Managers 2e, by Anthony Mersino.
Keywords: Project management -- Outlines, syllabi, etc.; elektronické knihy; electronic books